2012
DOI: 10.1155/2012/218642
|View full text |Cite
|
Sign up to set email alerts
|

Exon Dosage Variations in Brazilian Patients with Parkinson’s Disease: Analysis ofSNCA,PARKIN,PINK1andDJ-1Genes

Abstract: Abstract.Parkinson's disease is one of the most common neurodegenerative disorders associated with aging, reaching ∼ 2% of individuals over 65 years. Knowledge achieved in the last decade about the genetic basis of Parkinson's disease clearly shows that genetic factors play an important role in the etiology of this disorder. Exon dosage variations account for a high proportion of Parkinson's disease mutations, mainly for PARKIN gene. In the present study, we screened genomic rearrangements in SNCA, PARKIN, PIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…This corroborates the data presented by Moura et al 14 , who conducted research on Brazilian populations and quantified the SNCA gene mutations without finding any alterations. SNCA multiplications have been implicated in autosomal dominant forms of PD since 2003 15 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This corroborates the data presented by Moura et al 14 , who conducted research on Brazilian populations and quantified the SNCA gene mutations without finding any alterations. SNCA multiplications have been implicated in autosomal dominant forms of PD since 2003 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Remarkably, further Brazilian studies found no SNCA-A53T mutation in PD patients 14,18,19 . Furthermore, other genes re1ated to PD, such as APOE, GSTs and LRRK2 (PARK8), also showed no difference between patients and controls in this population 20,21,22,23 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For this reason, more than 200 putative pathogenic mutations have been reported worldwide, affecting numerous ethnic populations [33,35,59,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. The PARK2 mutation spectrum includes homozygous or compound heterozygous missense and nonsense point mutations, as well as several exon rearrangements (both duplications and deletions) involving all 12 exons and the promoter region.…”
Section: Park2mentioning
confidence: 99%
“…It is likely that the deletion results from an unequal crossing-over between these two sequences. Further heterozygous deletions involving exons 1, 3-8 and exon 7 have been described in familial or sporadic cases of early-onset PD [72,93,94].…”
Section: Pink1mentioning
confidence: 99%